Contribution of Ukrainian Scientists to the Development of Technology - Buyak, B.B.; Korsun, I.V.; Matsyuk, V.M. (Наука та інновації, 2019)
Introduction. Today, we can use phrase “the world’s first” for many inventions of Ukrainian scientists. Ukraine is a country with a high level of science development. As a proof of this statement, one may take the international recognition of achievements made by Ukrainian scientists in different areas of technology. Problem Statement. Ukraine aspires to become an equal member of the European Union. It is important that Ukrainians do not lose their national identity in this direction of movement. Disseminating knowledge about Ukrainian scientists is one of the ways to increase Ukraine's recognition in the world. That is why it is necessary to demonstrate to the world community the achievements of Ukrainian scientists and their high scientific level. Purpose. The research is aimed at justifying importance of Ukrainian scientists’ works for the development of technology in the world. Materials and Methods. The analytical review of the works of Ukrainian scientists that have the great importance for the development of technology in the world, was carried out. Results. The importance of Ukrainian scientists’ works in photography, cinematograph, electric welding, computer technology, aviation, astronomy, rocket science and astronautics has been proved. Ukrainian scientists were among the first in the invention of television, electric tram and radio control. Thanks to the work of our compatriots, it became possible to launch the first artificial satellite of the Earth, to make the flight of man to space, the exit of man in open space and landing on the surface of the Moon. Conclusions. Priority of Ukrainian scientists' works in many researches testifies to their significant contribution to the development of world technologies. Coverage of this contribution should by no means ignite interethnic animosity, but it can serve as an incentive to realize the national identity of Ukrainians in the context of world integration. The main principle is that science should unite peoples, and be the foundation of peace in the world. Given that Ukraine has significant achievements in science and technology, further research in this area is appropriate. Вступ. Сьогодні фразу «найперший у світі» можна застосувати для чималої кількості винаходів українських вче них. Україна є країною з високим рівнем розвитку науки, а доказом цього твердження є внесок українських науковців у різні галузі техніки. Проблематика. Україна прагне стати рівноправним членом Європейського Союзу. Важливо, щоб українці не втратили свою національну ідентичність при такому напрямку руху. Одним з шляхів підвищення впізнаваності України у світі є поширення знань про українських вчених через демонстрування світовій спільноті досягнень українських науковців та їх високого наукового рівня. Мета. Висвітлення важливості робіт українських науковців для розвитку техніки у світі. Матеріали й методи. Аналітичний огляд низки наукових робіт в галузі техніки. Результати. Досліджено внесок українських вчених у розвиток техніки у світі та проведено класифікацію відповідно до галузей. Показано важливість робіт українських науковців для розвитку фотографії, кінематографу, електричного зварювання, комп'ютерних технологій, авіації, астрономії, ракетної техніки та космонавтики. Українські вчені були серед перших у винаході телебачення, електричного трамваю та дистанційного керування об'єктами. Завдяки роботам наших співвітчизників став можливим запуск першого штучного супутника Землі, політ людини у космос, вихід людини у відкритий космос та приземлення на поверхню Місяця. Висновки. Пріоритетність робіт українських вчених у ряді досліджень свідчить про вагомий їх внесок у розвиток світових технологій. Висвітлення даного внеску в жодному разі не повинно розпалювати міжнаціональну ворожнечу, проте може слугувати стимулом для усвідомлення власної національної ідентичності українців в умовах світової інтеграції. При цьому, головним принципом є те, що наука має об'єднувати народи і бути фундаментом миру у світі. Зважаючи на те, що Україна має вагомі досягнення у науці й техніці, доцільними є подальші дослідження у зазначеному напрямку. Введение. Сегодня фразу «первый в мире» можно использовать для многих изобретений украинских ученых. Украина является страной с высоким уровнем развития науки. Доказательством этого утверждения является вклад ук раинских ученых в различные отрасли техники. Проблематика. Украина стремится стать равноправным членом Европейского Союза. Важно, чтобы украинцы не утратили свою национальную идентичность при этом направлении движения. Распространение знаний об украинских ученых является одним из путей повышения узнаваемости Украины в мире. Поэтому необходимо демонстрировать мировому сообществу достижения украинских ученых и их высокий научный уровень. Цель. Oбоснование важности работ украинских ученых для развития техники в мире. Материалы и методы. Аналитический обзор ряда научных работ в области техники. Результаты. Доказана важность работ украинских ученых для развития фотографии, кинематографа, электрической сварки, компьютерных технологий, авиации, астрономии, ракетной техники и космонавтики. Украинские ученые были среди первых в изобретении телевидения, электрического трамвая и дистанционного управления объектами. Благодаря работам наших соотечественников стал возможным запуск первого искусственного спутника Земли, полет человека в космос, выход человека в открытый космос и приземления на поверхность Луны. Выводы. Приоритетность работ украинских ученых в ряде исследований свидетельствует о весомом их вкладе в развитие мировых технологий. Освещение этого вклада ни в коем случае не должно разжигать межнациональную рознь, однако может служить стимулом для осознания собственной национальной идентичности украинцев в условиях мировой интеграции. Главным принципом является то, что наука должна объединять народы и быть фундаментом мира. Украина имеет весомые достижения в науке и технике, а поэтому целесообразно проводить дальнейшие исследования в указанном направлении.